2008
DOI: 10.1016/j.virol.2008.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic determinants of a tick-borne flavivirus associated with host-specific adaptation and pathogenicity

Abstract: Tick-borne flaviviruses are maintained in nature in an enzootic cycle involving a tick vector and a vertebrate host. Thus, the virus replicates in two disparate hosts, each providing selective pressures that can influence virus replication and pathogenicity. To identify viral determinants associated with replication in the individual hosts, plaque purified Langat virus (TP21pp) was adapted to growth in mouse or tick cell lines to generate two virus variants, MNBp20 and ISEp20, respectively. Virus adaptation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
(57 reference statements)
4
25
0
Order By: Relevance
“…These results confirm the results of the authors' previous studies (20,26) as well as other studies that showed replication of highly virulent strains of TBEV starting from 12 h pi by using different cell cultures (31,35,45,52).…”
Section: Dynamics Of Infection Of Donors' Blood Cells By Tbev Strainssupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm the results of the authors' previous studies (20,26) as well as other studies that showed replication of highly virulent strains of TBEV starting from 12 h pi by using different cell cultures (31,35,45,52).…”
Section: Dynamics Of Infection Of Donors' Blood Cells By Tbev Strainssupporting
confidence: 92%
“…The key to understanding how these viruses are able to evade the host's immune response and make their way from the site of infection to the central nervous system and the brain is studying viral-host cell interactions. Mutational analyses of the flaviviral envelope E protein, which is critical for cellular infectivity, have demonstrated a striking ability of flaviviruses to adapt to different cells and receptors (2,11,31). In this study, the interaction between TBEV and human blood leukocytes was examined, since it is known that these cells could differently contribute to the protective and pathogenic manifestations of flavivirus infections (4,28,32,37).…”
Section: Introductionmentioning
confidence: 99%
“…Langat virus has a low virulence for humans, although it shares more than 74% nucleotide identity with TBEV. Experimental models on LGTV in mice have been reported (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of LGTV is in part determined by genetic determinants of the virus that are involved in mechanisms of host adaptation (19). Genetic determinants of the host, for example, genes of the tlr family, may also control virus infection in neurons, possibly by regulating neuroinflammatory responses (20).…”
Section: Introductionmentioning
confidence: 99%
“…A control replicon construct with NS5 catalytic aspartate residue deletions was transfected in parallel as a negative control. At 3,6,12,24,48,72,96, and 120 h posttransfection, the medium was removed and cells were washed with phosphate-buffered saline and lysed with 100 l of 1ϫ Renilla lysis buffer from the Renilla Luciferase Assay System (Promega, Madison, WI). The lysates were stored at Ϫ80°C.…”
mentioning
confidence: 99%